2003
DOI: 10.1002/jbm.b.10053
|View full text |Cite
|
Sign up to set email alerts
|

Wear evaluation of cobalt–chromium alloy for use in a metal‐on‐metal hip prosthesis

Abstract: Wear of the polyethylene in total joint prostheses has been a source of morbidity and early device failure, which has been extensively reported in the last 20 years. Although research continues to attempt to reduce the wear of polyethylene joint-bearing surfaces by modifications in polymer processing, there is a renewed interest in the use of metal-on-metal bearing couples for hip prostheses. Wear testing of total hip replacement systems involving the couple of metal or ceramic heads on polymeric acetabular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…The number of loading cycles varies typically from 3 up to 10 Mcycles at frequencies of 1 or 1.13 Hz. Table 2 summarizes the key features of published papers on the characterisation of metal on metal CoCrMo artificial hip joints using simulators [12,[46][47][48][49][50][51][52][53][54][55][56][57][58]. Among the authors, only Yan [49] measured the evolution of open circuit potential during a simulator test.…”
Section: Simulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of loading cycles varies typically from 3 up to 10 Mcycles at frequencies of 1 or 1.13 Hz. Table 2 summarizes the key features of published papers on the characterisation of metal on metal CoCrMo artificial hip joints using simulators [12,[46][47][48][49][50][51][52][53][54][55][56][57][58]. Among the authors, only Yan [49] measured the evolution of open circuit potential during a simulator test.…”
Section: Simulatorsmentioning
confidence: 99%
“…With approximately 40 components [63] bovine serum is a very complex liquid with a broad reactivity spectrum. It is seldom used without additions of biocides (such as sodium azide NaN 3 ) and complexing agents (such as EDTA) to avoid metal precipitation [46][47][48]51,[53][54][55][56][57]. Moreover, it can be used at different dilutions in water [51] or Ringer's solutions [52] depending on laboratory.…”
Section: Simulatorsmentioning
confidence: 99%
“…Both in vitro and in vivo studies have suggested that there may be considerable differences in material wear and implant failure rates based on whether implants are manufactured using a wrought, cast or heated-cast process, although the published results are contradictory [47,[57][58][59][60]. However, several authors have reported improved wear characteristics and survival rates of high carbon versus low carbon cobalt-chromium alloys in metal-on-metal hip resurfacing arthroplasties [54,56,61,62]. The commercial introduction of highly cross-linked polyethylene has reduced wear rates, with one in vitro study reporting volumetric wear rates of 3 mm 3 per million cycles compared with 48 mm 3 per million cycles before cross-linking [11].…”
Section: Potential Benefits Of Metal-on-metal Articulationsmentioning
confidence: 93%
“…After an initial run-in period over the first 1-2 years, during which time linear wear rates of 20-25 µm/year have been reported, a low steady-state linear wear rate of 2.5-10 µm/year is usually achieved [25,52,53]. This translates into a 20-180-times lower linear wear rate compared with conventional metal-onpolyethylene bearings [25,54], although because of the considerably smaller mean size of metal wear particles, the number of wear fragments is typically greater [55,56]. Even with modern metal-on-metal bearings, there is considerable heterogeneity in metallurgical properties, with variability in alloy composition and manufacturing techniques.…”
Section: Potential Benefits Of Metal-on-metal Articulationsmentioning
confidence: 94%
“…The volumetric wear rates of CoCr alloys are affected by the carbide content and the material combinations used, with the wear rate decreasing (pin-on-disc experiments) from a low-carbide head/lowcarbide cup (5.6 ± 2.4 mg) to a low-carbide head/ high-carbide cup (1.4 ± 0.9 mg) to a high-carbide head/ high-carbide cup (1.3 ± 0.6 mg) [34]. The in vivo wear rate of Metasul 1 (Sulzer Medica, Winterthur, Switzerland) bearings (high-carbide head/high-carbide cup) showed a steady-state wear rate of 2 to 5 lm per year [3,30], whereas a higher wear rate of 7.6 lm per year was reported for Sikomet TM (from a low-carbide head/low-carbide cup) bearing couples [29].…”
Section: Introductionmentioning
confidence: 99%